Playing without goalkeeper : the use of an empty goal in high performance men's handball - Macedo, Luís Manuel Teles (2022)
This study aims to characterize the context of use of empty goal (EG) rule in handball; to assess the risk of conceding a goal in an empty net; to identify the performance variables that influence the efficacy of EG attacks; and to analyse the use of EG according to the national team. A new observational tool has been developed for the analysis of EG attacks. A total of 974 EG attacks were sampled from 65 matches of the 2022 European Men's Handball Championship. A frequency analysis and the chisquare test have been performed to analyse the use of EG according to the match context. The binominal logistic regression was used to identify the variables that influence the efficacy of EG attacks. The results demonstrated that goalkeeper (GK) was replaced mainly to maintain the numerical equality. To create superiority in attack the teams mostly used EG during the last quarter of match playing under a small score disadvantage. The risk of conceding a goal in the empty net was higher when a team failed to score in previous possession. No relationship was found between team’s final classification and frequency of EG use. Two variables have been identified as significant for the 6x6+GK possession outcome: the 2nd pivot position and the shot zone.